A brief rituximab, bendamustine, mitoxantrone (R‐BM) induction followed by rituximab consolidation in elderly patients with advanced follicular lymphoma: a phase II study by the Fondazione Italiana Linfomi (FIL). (21st January 2021) - Boccomini, Carola; Ladetto, Marco; Rigacci, Luigi; Puccini, Benedetta; Rattotti, Sara; Volpetti, Stefano; Ferrero, Simone; Chiarenza, Annalisa; Freilone, Roberto; Novo, Mattia; Corradini, Paolo; Nassi, Luca; et al.
Summary: Treatment for follicular lymphoma (FL) in the elderly is not well standardized. A phase II, multicentre, single arm trial was conducted in this setting with a brief chemoimmunotherapy regimen. Treatment consisted in four monthly courses of rituximab, bendamustine and mitoxantrone (R‐BM) followed by 4 weekly rituximab as consolidation; rituximab maintenance was not applied because the drug was not licensed at the time of enrolment. The primary endpoint was the complete remission rate (CR). Seventy‐six treatment‐naive FL patients (aged 65–80 and a "FIT" score, according to the Comprehensive Geriatric Assessment) were enrolled. CR was documented in 59/76 patients (78%), partial remission in 12 (16%) and stable/progressive disease in five (6%) with an overall response rate in 71/76 (94%). Median follow‐up was 44 months with 3‐year progression‐free‐survival (PFS) and overall‐survival of 67% and 92% respectively. Nine deaths occurred, three of progressive disease. The regimen was well tolerated and the most frequent severe toxicity was neutropenia (18% of the cycles). Bcl‐2/IGH rearrangement was found in 40/75 (53%) of evaluated patients. R‐BM was highly effective in clearing polymerase chain reaction‐detectable disease: 29/31 (96%) evaluated patients converted to bcl‐2/IGH negativity at the end of treatment. A brief R‐BM regimen plus rituximab consolidation is effective and safe in "FIT" elderly, treatment‐naïve, FL patients, inducing high CR and molecular remission rates with prolonged PFS.